Isoflavones and a Phenylethanoid from Verbascum sinatiticum - Elgindi , M.R.; Melek, F.R.; Miyase, T.; Mabry, T.J. (Asian Journal of Chemistry, 2012)
Four isoflavone glycosides, orobol, orobol 7-0-b-D-glucoside and two new glycosides of known aglycones, namely, 5,3',4'-trihydroxy-8-methyl-isoflavone 7-0-b-D-glucoside, 5-hydroxy-3',4'-dimethoxyisoflavone 7-0-a-L-rthamnoside were isolated and identified from the aerial parts of Verbascum sinaiticum. In addition, the phenylethanoid glycoside, acteoside, was alsodetected. The structures of all compounds were established by chromatographic and spectroscopic methods. This is the first report of isoflavanes from Verbascum sinaiticum.